2014
DOI: 10.14740/jem243w
|View full text |Cite
|
Sign up to set email alerts
|

Significant Differences in Effects of Sitagliptin Treatment on Body Weight and Lipid Metabolism Between Obese and Non-Obese Patients With Type 2 Diabetes

Abstract: Background: We previously reported that HbA1c levels and body weight significantly decreased by 0.6% and by 0.8 kg, respectively, at 6 months after sitagliptin treatment started. We found a significant and negative correlation between change in body weight and body mass index (BMI) at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…(TABLE 3). Table 3 Result of our study is comparable to the studies conducted by Katsuyama et al [2] who had observed that Body weight and BMI in obese group were significantly greater than in non- Yanai et al [3] had found a significant and negative correlation between change in body weight and body mass index at baseline. After 6 months they found a significant reduction in body weight.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…(TABLE 3). Table 3 Result of our study is comparable to the studies conducted by Katsuyama et al [2] who had observed that Body weight and BMI in obese group were significantly greater than in non- Yanai et al [3] had found a significant and negative correlation between change in body weight and body mass index at baseline. After 6 months they found a significant reduction in body weight.…”
Section: Resultssupporting
confidence: 88%
“…Other comparative studies reveal comparison of Lipid profiles include a study performed by Chawla S. et al [12] revealed a significant (p<0.01) decrease in High density lipoprotein (HDL-C) & a significant (p<0.01) decrease in Triglyceride, whereas Katsuyama et al [2] had also established that significant differences was seen in effects of Sitagliptin treatment on Another study performed by Sakamoto Y. et al [13] had demonstrated that serum levels of triglycerides and total cholesterol decreased significantly. (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Result of our study is comparable to the studies conducted by Katsuyama et al [2] who had observed that Body weight and BMI in obese group were significantly greater than in nonobese group at baseline. After 6 months of initiating sitagliptin use, significant reduction in body weight in obese group, whereas no change was noted in non-obese group, whereas…”
Section: Methodssupporting
confidence: 90%
“…Other comparative studies reveal comparison of Lipid profiles include a study performed by Chawla S. et al [12] revealed a significant (p<0.01) decrease in High density lipoprotein (HDL-C) & a significant (P<0.01) decrease in Triglyceride, whereas Katsuyama et al [2] had also established that significant differences was seen in effects of sitagliptin treatment on body weight and lipid metabolism between obese and non-obese patients with type 2 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Katsuyama ve ark. [14] Tip 2 diyabetik obez ve obez olmayan bireyler üzerinde yaptiklari çalişmalarinda, sitagliptinin vücut ağirliğini azaltiğini bildirmişlerdir.…”
Section: Introductionunclassified